Pengaruh Biaya Operasional, Pendapatan Operasional, Non Performing Financing dan Financing to Deposit Ratio terhadap Return on Asset - Muthi'ah Afifah Fauziah; Nana Diana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to examine the effect of BOPO, NPF, and FDR on Profitability described by ROA at Islamic Commercial Banks registered with OJK for the 2016-2020 period. Sampling using purposive sampling and obtained 7 Islamic Commercial Banks that meet the criteria of 14 Islamic Commercial Banks as a sample. So the number of samples studied is 35 data for 5 years. This research method uses quantitative methods. The approach used in this study is a descriptive and verification approach. Based on the results of research conducted using SPSS 20, it can be concluded both partially and simultaneously, namely. BOPO has a negative and significant effect on return on assets, NPF has a positive and significant effect on return on assets and FDR has a positive and significant effect on return on assets while simultaneously BOPO, NPF, FDR have a significant effect on return on assets in Islamic commercial banks in Indonesia Registered at OJK for the 2016-2020 period. In this study, it shows that the variables studied, namely BOPO, NPF and FDR, can describe 92.6% of Return On Assets (ROA). Keywords: BOPO, NPF, FDR, ROA